GAMBARAN KONSUMSI ZAT BESI, SENG DAN STATUS GIZI PADA ANAK SEKOLAH DASAR DI SDN NO.060813 KELURAHAN PASAR MERAH BARAT KECAMATAN MEDAN KOTA TAHUN 2014 - Fadhlan Mulia A Harahap; Etti Sudaryati; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Indonesia still faces major challenges in the field of nutrition, namely malnutrition and nutrition, nutritional status of primary school children is a picture of what is consumed in the long term. One problem that often occurs is the consumption of iron and zinc, so that the necessary attention in the consumption of foods and nutrients are school-age children. This study aims to describe the consumption of iron, zinc and nutritional status of primary school children in SDN No. 060813 Kelurahan Pasar Merah Barat Kecamatan Medan Kota. This type of research is a survey research using quantitative approach. Sampling was carried out with a total sampling method with a sample of 69 students. The type of data collected primary data, performed by using interviews, questionnaires 24 hour recall, food frequency and measurement of nutritional status (TB/U and IMT/U) and secondary data obtained diinstansi related, processing and analysis of data by using a computer program SPSS, Nutrisurvey and WHO antro plus 2007. The results showed that the consumption of iron in school children in SDN 060 813 Kelurahan Pasar Merah Barat Kecamatan Medan Kota largely on the category of less as many as 39 people (56.5%), consumption of zinc mostly in the category of less as many as 52 people (75 , 4%), nutritional status based on IMT/U mostly in the normal category as many as 57 people (82.6%), based on the nutritional status of TB/U mostly in the normal category as many as 44 people (63.8%) The results of this study may be a referral for students to consume a varied diet and nutrition, and to other researchers to further explore the different variables. Keywords: Elementary School Children, Consumption Iron, Zinc Nutritional Status